2020
DOI: 10.1038/s41598-020-73477-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to low-dose DBP in the mice induces obesity in offspring via suppression of UCP1 mediated ER stress

Abstract: Dibutyl phthalate (DBP) is recognized as an environmental endocrine disruptor that has been detected in fetal and postnatal samples. Recent evidence found that in utero DBP exposure was associated with an increase of adipose tissue weight and serum lipids in offspring, but the precise mechanism is unknown. Here we aimed to study the effects of in utero DBP exposure on obesity in offspring and examine possible mechanisms. SPF C57BL/6J pregnant mice were gavaged with either DBP (5 mg /kg/day) or corn oil, from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
1
13
2
Order By: Relevance
“…Decreased serum levels of triglyceride, fasting glucose, prolactin, HOMA-IR were also found in female offspring, but no difference for fasting insulin, total cholesterol, and adiponectin. Being consistent with the results of present study, intrauterine exposure to low-dose DBP (5 mg/kg/day) from GD 12 until PND 7 also promoted obesity in adult female and male offspring, but with evidence of glucose and lipid metabolic disorders and a decreased metabolic rate (Li et al, 2020). Xiong et al (2020) also found the body weight of mice was increased after exposure to both low and high doses of DBP (0.1 and 1 mg/kg) by oral gavage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased serum levels of triglyceride, fasting glucose, prolactin, HOMA-IR were also found in female offspring, but no difference for fasting insulin, total cholesterol, and adiponectin. Being consistent with the results of present study, intrauterine exposure to low-dose DBP (5 mg/kg/day) from GD 12 until PND 7 also promoted obesity in adult female and male offspring, but with evidence of glucose and lipid metabolic disorders and a decreased metabolic rate (Li et al, 2020). Xiong et al (2020) also found the body weight of mice was increased after exposure to both low and high doses of DBP (0.1 and 1 mg/kg) by oral gavage.…”
Section: Discussionsupporting
confidence: 93%
“…Perinatal phthalate exposures are associated with short-and long-term activation of PPAR target genes in liver tissue, which manifested as increased fatty acid production in early postnatal life and increased fatty acid oxidation in adulthood (Neier et al, 2020). Intrauterine exposure of mice to low-dose DBP (5 mg/kg/day) appears to promote obesity in offspring by inhibiting UCP1 via endoplasmic reticulum stress (higher expression of Bip and Chop), a process that is largely reversed by treatment with TUDCA (Li et al, 2020). DBP aggravate type 2 diabetes by disrupting the insulin signaling pathway and impairing insulin secretion.…”
Section: The Glycolipid Metabolism Of F1 Female Offspringmentioning
confidence: 99%
“…In the mice on a 12-week HFD, the HFD contributed to obesity development in general; moreover, doxepin promoted body, RWAT, EWAT, kidney, and liver weight gain. Moreover, the body fat increases may have been attributable to decreased uncoupling protein 1 (UCP1) mRNA expression in brown adipose tissue ( Figure S2), and UCP1 can increase energy expenditure by regulating the metabolic rate [45]. In addition, leptinessential in food intake regulation in the hypothalamus-is primarily synthesized in WAT [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant mouse dams were exposed to DBP from the 12th day of gestation to one week after birth. 4- to 5-month-old mice from the DBP group exhibited higher body weight, lower expression of UCP1, insulin insensitivity, greater endoplasmic reticulum stress, and levels of inguinal and epididymal WAT that were twice as high as controls ( 136 ). DBP exposure caused insulin resistance, suggesting the presence of a pre-diabetic condition which is often a comorbidity in obese individuals.…”
Section: Dibutyl Phthalatementioning
confidence: 97%
“…DBP exposure caused insulin resistance, suggesting the presence of a pre-diabetic condition which is often a comorbidity in obese individuals. Lower UCP1 levels impair the production of heat by thermogenic tissues and increased endoplasmic reticulum stress, greatly affecting mitochondrial function ( 136 ). Offspring of DBP-treated mice also showed significantly higher levels of binding immunoglobulin protein (Bip), and CCAAT/enhancer-binding protein homologous protein (Chop), which are two markers of ER stress that were associated with lower UCP1 levels.…”
Section: Dibutyl Phthalatementioning
confidence: 99%